Raspberry Pi image processing programming develop real-life examples with Python, Pillow, and SciPy - Pajankar, Ashwin (Apress, 2017)
Write your own Digital Image Processing programs with the use of pillow, scipy.ndimage, and matplotlib in Python 3 with Raspberry Pi 3 as the hardware platform. This concise quick-start guide provides working code examples and exercises. Learn how to interface Raspberry Pi with various image sensors. What You Will Learn: •Understand Raspberry Pi concepts and setup •Understand digital image processing concepts •Study pillow, the friendly PIL fork •Explore scipy.ndimage and matplotlib •Master use of the Pi camera and webcam.
Online resource; title from cover (Safari, viewed April 20, 2017)
Keywords: Image processing -- Digital techniques; Python (Computer program language); Raspberry Pi (Computer); Traitement d'images; Techniques numériques; Python (Langage de programmation); Raspberry Pi (Ordinateur); digital imaging; Image processing; Digital techniques